Love, freedom and evil : does authentic love require free will? - Thaddeus, J. Williams. (Currents of Encounter, 2011)
The defining premise of the Relational Free Will Defense is the claim that authentic love requires free will. Many scholars, including Gregory Boyd and Vincent Brümmer, champion this claim. Best-selling books, such as Rob Bell's Love Wins , echo that love "cannot be forced, manipulated, or coerced. It always leaves room for the other to decide." The claim that love requires free will has even found expression in mainstream Hollywood films, including Frailty , Bruce Almighty , and The Adjustment Bureau . The analysis shows convincingly that the claim that authentic love requires free will, does not meet the criteria of consistency, compatibility with Scriptural sources, and the demands of concrete encounter with problems of moral evil.